Intra-individual variability and continuity of action and perception measures in infants - Gampe, Anja; Keitel, Anne; Daum, Moritz M. (Frontiers in Psychology, 2015)
The development of action and perception, and their relation in infancy is a central research area in socio-cognitive sciences. In this Perspective Article, we focus on the developmental variability and continuity of action and perception. At group level, these skills have been shown to consistently improve with age. We would like to raise awareness for the issue that, at individual level, development might be subject to more variable changes. We present data from a longitudinal study on the perception and production of contralateral reaching skills of infants aged 7, 8, 9 and 12 months. Our findings suggest that individual development does not increase linearly for action or for perception, but instead changes dynamically. These non-continuous changes substantially affect the relation between action and perception at each measuring point and the respective direction of causality. This suggests that research on the development of action and perception and their interrelations needs to take into account individual variability and continuity more progressively.